2020
DOI: 10.3390/ma13081843
|View full text |Cite
|
Sign up to set email alerts
|

Safety Considerations for Thermoplastic-Type Appliances Used as Orthodontic Aligners or Retainers. A Systematic Review and Meta-Analysis of Clinical and In-Vitro Research

Abstract: Use of thermoplastic material in orthodontics, either as aligner or as retainer appliances, is common practice and is likely to increase in the years to come. However, no systematic assessment on safety considerations of these adjuncts has been implemented up to date. The aim of this systematic review was to collectively appraise the existing evidence from both clinical and laboratory studies, on whether these appliances are associated with any estrogenic/cytotoxic effects or bisphenol-A (BPA) and monomer leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…Biocompatibility and application material safety are essential factors, which should be considered during aligner therapy. However, a recent meta-analysis on safety considerations of orthodontic aligners revealed that the current evidence is inconsistent, and further laboratory and clinical studies are needed [ 10 ]. A potential cytotoxic effect of aligners’ eluates was tested in several in vitro studies, reporting rather weak cytotoxic activity of aligner eluates toward gingival fibroblasts, keratinocytes, and breast cancer cells [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility and application material safety are essential factors, which should be considered during aligner therapy. However, a recent meta-analysis on safety considerations of orthodontic aligners revealed that the current evidence is inconsistent, and further laboratory and clinical studies are needed [ 10 ]. A potential cytotoxic effect of aligners’ eluates was tested in several in vitro studies, reporting rather weak cytotoxic activity of aligner eluates toward gingival fibroblasts, keratinocytes, and breast cancer cells [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all, adoption of occupational measures in dental practice against potentially hazardous aerosol-forming procedures should be considered in a universal basis, and standard precaution procedures should involve more skeptical application and even reduction in the use of aerosol-forming instrumentation in everyday practice. These constitute not only ultrasonic scaling but also restorative procedures (Purohit et al 2009), enamel cleanup after fixed appliance orthodontic treatment (Dawson et al 2016), and massive attachment removal following aligner treatment (Iliadi et al 2020). To this respect, founding recommendations from the US Centers for Disease Control and Prevention (2016) involve a range of safety considerations, as documented by aerosol and waterline precautions, personal protective equipment, and ventilation management.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosolized microorganisms, including potentially airborne pathogens, may come as a result of the active performance of high-powered handpiece utilization during standard dental procedures. Tooth grinding for restorations, material grinding, composite removal after orthodontic debonding, attachment grinding after aligner treatment (Iliadi et al 2020), and routine practice professional oral prophylaxis with high-speed ultrasonic scalers are adequately matched for an increased dynamic for spatter-related contamination within the dental practice environment and across the practices’ personnel (Laheij et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clear aligners, a series of clear plastic appliances, represent an esthetic and removable alternative to conventional fixed orthodontic treatment. Reinforced by the patients' request for less visible orthodontic devices and a systematic promotion policy of aligner companies, an increased demand for clear aligner treatment took place in the last decade [1][2][3]. This led to an intensified development and application of this orthodontic treatment modality [4].…”
Section: Introductionmentioning
confidence: 99%